The wife and the widow - White, Christian (Minotaur Books, 2020)
"The second standalone thriller from the award-winning author of The Nowhere Child, Christian White. Set against the backdrop of an eerie island town in the dead of winter, The Wife and The Widow is an unsettling thriller told from two perspectives: Kate, a widow whose grief is compounded by what she learns about her dead husband's secret life; and Abby, an island local whose world is turned upside when she's forced to confront the evidence of her husband's guilt. But nothing on this island is quite as it seems, and only when these women come together can they discover the whole story about the men in their lives. Brilliant and beguiling, The Wife and The Widow takes you to a cliff edge and asks the question: how well do we really know the people we love?"--